Tutela contra sentencias. Procedencia y modalidades jurisprudenciales en Colombia (1992-2006) (2009)
The tutela action against judicial decisions is the most conflictive issue in the confrontation among the diverse jurisdictions that integrate the administration of justice in Colombia. This phenomenon has been qualified by the mass media as “collision of trains”. The traditional functional separation between jurisdictions, which is founded in the autonomy of the different juridical disciplines, has been questioned by the integration constitutional vision, by virtue of which all judges, despitethe jurisdiction to which they belong to, must apply the Constitution,especially for the protection of the fundamental rights, which is achieved by means of the tutela action. Therefore, the convergence of all jurisdictions in the constitutional jurisdiction is set out.